PERBEDAAN DIGITAL WELLBEING SISWA SMK DITINJAU DARI GENDER - Nur atikah; Frischa Meivilona Yendi (STKIP Subang, 2026)
Along with the increasing intensity of digital technology use among vocational high school (SMK) students, understanding of the quality of students' relationship with the technology they use every day becomes important, a condition known as digital wellbeing. This study was conducted to describe the picture of digital wellbeing of male and female students and to find out whether there is a difference in digital wellbeing between the two groups. This study used a quantitative approach with a comparative descriptive method. The subjects to active students of grade XI and XII at a public vocational high school. Data were collected using the Perceived Digital wellbeing in Adolescence Scale that had been adapted into Indonesian, then analyzed descriptively and tested using the Independent Sample T-Test. The results showed that the digital wellbeing of both male and female students was in the moderate category, both overall and on the social, cognitive, and emotional aspects, and there was no significant difference between the two groups. This finding shows that gender is not the main factor that differentiates the level of digital wellbeing of vocational high school students, so guidance and counseling services related to digital wellbeing can be given equally to all students regardless of gender.